JAEPL, Vol. 20, Winter 2014-2015 - Joonna Smitherman Trapp; Bradley T. Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Essays Libby Falk Jones - Praisesong: One (Worn) Path through AEPL Alice Brand - Twenty Years: Reflections and Questions Tom Gage - Hitchhiking the Labyrinth Susan Schiller - The Dance of Spirit in AEPL Kristie S. Fleckenstein - Stepping Beyond, In, and With JAEPL: Twenty Years of Hope Paul Heilker - Coming to Nonviolence Beth Daniell - To the Contrary John Creger - The Personal Creed Project: Portal to Deepened Learning Jessica Jones - "Put Your Ear Close to the Whispering Branch..." Deep Listening in the English Classroom Out of the Box Laurence Musgrove & Myra Musgrove - Drawing is Learning Book Reviews Judy Halden-Sullivan - Embracing the "Beginner's Mind" Elizabeth French - Richardson, Scott. eleMENtary School—(Hyper) Masculinity in a Feminized Context. Rotterdam: Sense Publishers, 2012. Print. Brad Lucas - Ryden, Wendy and Ian Marshall. Reading, Writing, and the Rhetorics of Whiteness. NY: Routledge, 2012. Print. Candace Walworth - Kroll, Barry. The Open Hand: Arguing as an Art of Peace. Logan, UT: Utah State UP, 2013. Print. Caleb Corkery - Conway, Jeremiah. The Alchemy of Teaching: The Transformation of Lives. Boulder, CO: Sentient Publications, 2013. Print. Connecting Helen Walker - Widening Circles Wanda Njoya - Miracles Happen Ann Wachira - Using a Model David Bedsole - To the Dog Next Door Who Barks All Day W. Keith Duffy - Aisle Four: Ice Cream, TV Dinners, Humility